Effects of Aerosol Mixing States on the Aerosol Multiple Scattering Properties and the Light Transmittances - Yuzhao Ma; Wenrong Liu; Huiliang Gao; Jiaqi Liu; Meng Li; Xinglong Xiong (IEEE Photonics Journal, 2019)
The scattering properties of atmospheric aerosols may be sensitive to the mixing states of the aerosols. Based on the internal and external mixing models of the aerosols, we have numerically simulated the transmissions of the light through mixed aerosols using the Monte-Carlo method. For the first time, the multiple scattering properties of mixed aerosols are discussed for different mixing states of the aerosol systems composing of black carbon and sulfate, considering different sizes of the black carbon particle. The simulation results show that the mixing states may significantly affect the multiple scattering properties of aerosols, hence, the light transmittances. The presented work is useful for better understanding the light transmission through the actual aerosols.